Shape‐ and Size‐Controlled Synthesis of Mn3O4 Nanocrystals at Room Temperature. Issue 19 (27th May 2014) - Chen, Chao; Jian, Hong; Mai, Kaiguang; Ren, Zhimin; Wang, Jia; Fu, Xinxin; Fan, Chenyao; Sun, Chunxiao; Qian, Guodong; Wang, Zhiyu
Abstract: A versatile synthetic method has been developed for the fabrication of Mn3 O4 nanocrystals with different sizes and shapes, such as square nanoplates, mesocrystal nanodisks, and nanopolyhedra. Manganese(II) acetate tetrahydrate and hydrazine monohydrate were the only two reactants used in aqueous solution, and no surfactant was employed. The key advantages of our approach are (1) the room‐temperature synthesis, (2) the facile operation, (3) the flexibility in shape‐ and size‐control, and (4) the ease of scale‐up. The exposed surfaces of the as‐prepared nanoparticles were carefully characterized and indexed. The catalytic properties of the nanoplates for the degradation of methylene blue were evaluated in detail. The catalytic properties are closely related to the shape and size of the Mn3 O4 nanocrystals, and nanoplates with a size of 50 nm exhibited the best catalytic performance. The magnetic properties were investigated with a superconducting quantum interference device magnetometer. Abstract : A versatile strategy has been developed for the fabrication of Mn3 O4 nanocrystals with different sizes and shapes (square nanoplates, mesocrystal nanodisks, nanopolyhedra). The central advantages of this approach are that it is performed at room temperature, facile, and easily scaled up.